The production of video-classes as a learning tool to the animal anatomy discipline - Schoenau, Luciana Silveira Flores; Schoenau, William (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The anatomy study has been a challenge lately. The use of animals in education has been a difficult due by moral and ethical issues and the 3R’s chain (reduce, recycle and reuse), which makes it difficult the acquisition of anatomical parts and the manipulation of them by the students. This issue affected directly the more traditional and effective methodology of learning anatomy: the dissection. Allied to these factors, the students of higher education belong to a technological generation, spending much of their time in front of the computer and using digital equipment. The search of new technologies of anatomical education is now a reality. The aim of this research was to produce a learning tool through video and to evaluate its use by students of Veterinary Medicine. The video production of different issues was proposed to groups of at least three students as part of the evaluation of the subject. The students have answered a survey based on a five-point Likert scale and the results have been analyzed by qualitative and quantitative ways. The results have been favorable for the use of video as a learning tool and a way of group integration.